Studies on the mechanism of action of dioctyl sodium sulphosuccinate in the human jejunum. Issue 10 (October 1985) - Moriarty, K J; Kelly, M J; Beetham, R; Clark, M L
Abstract : An intestinal perfusion technique has been used to investigate the mechanism of action of the laxative, dioctyl sodium sulphosuccinate, in the human jejunum. Dioctyl sodium sulphosuccinate stimulated net secretion of water, sodium, chloride and potassium and inhibited net absorption of glucose and bicarbonate. These changes in water and solute transport were partially reversed by administration of indomethacin (4 mg/kg/day orally for three days), which suggests that they are mediated in part by endogenous prostaglandins.